2020
DOI: 10.1155/2020/3283940
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Conservative Treatment without Early Colonoscopy in Patients with Colonic Diverticular Hemorrhage

Abstract: Aim. This study was aimed to clarify the effectiveness of conservative treatment without performing early colonoscopy and the indications for early colonoscopy in patients with colonic diverticular hemorrhage. Methods. This retrospective study included 142 participants who were urgently hospitalized due to bloody stools and were diagnosed with colonic diverticular hemorrhage between April 2012 and December 2016. At the time of hospital visit, only when both shock based on vital signs and intestinal extravasati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…According to Doi et al who studied 142 patients with CDB, in cases of both shock and positive CT extravasation, two of five patients developed severe bleeding who required hemostasis with IR. 24 In a report by Nakatsu et al who studied 346 patients with CDB, the rate of bleeding source identification in emergency colonoscopy was 68% for positive extravasation and 20% for negative extravasation, and it was significantly higher for those with positive extravasation. 25 Shock and positive extravasation strongly indicate massive or active bleeding, and rapid hemostatic treatment is necessary while maintaining the vital signs in an emergency situation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Doi et al who studied 142 patients with CDB, in cases of both shock and positive CT extravasation, two of five patients developed severe bleeding who required hemostasis with IR. 24 In a report by Nakatsu et al who studied 346 patients with CDB, the rate of bleeding source identification in emergency colonoscopy was 68% for positive extravasation and 20% for negative extravasation, and it was significantly higher for those with positive extravasation. 25 Shock and positive extravasation strongly indicate massive or active bleeding, and rapid hemostatic treatment is necessary while maintaining the vital signs in an emergency situation.…”
Section: Discussionmentioning
confidence: 97%
“… 23 Both are findings that indicate active bleeding for CDB. According to Doi et al who studied 142 patients with CDB, in cases of both shock and positive CT extravasation, two of five patients developed severe bleeding who required hemostasis with IR 24 . In a report by Nakatsu et al who studied 346 patients with CDB, the rate of bleeding source identification in emergency colonoscopy was 68% for positive extravasation and 20% for negative extravasation, and it was significantly higher for those with positive extravasation 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Further real-world data on conservative management of patients hospitalized with LGIB is needed given the high number of colonoscopies performed and the correspondingly low rate of endoscopic intervention. In a single-center, retrospective report of 142 consecutive patients with LGIB, conservative management, based on an elective colonoscopy within 2 weeks after spontaneous hemostasis in patients who had an initial negative CTA and did not present with shock, was an effective management strategy (141). In a retrospective cohort of 97 patients with stable LGIB, 38% of the cohort was discharged early from the ED with outpatient management; factors associated with early discharge included younger age, lack of antithrombotic medications, higher index hemoglobin and albumin, and lower BUN and creatinine scores.…”
Section: Timing Of Colonoscopymentioning
confidence: 99%
“…[37] Recent reports regarding early colonoscopy for diverticular hemorrhage recommend conservative treatment except in severe cases, as the identification rate of SRH was 15% to 42% and the early and late rebleeding rates were not significantly different compared to patients who were treated conservatively. [36][37][38][39] In contrast, the identification rate of the bleeding source by angiography is estimated to be 25% to 75%. [13,40,41] In the current study, the identification rate of the bleeding source by angiography was 66.7%, which was considered effective for patients with repeated rebleeding in whom the bleeding source was not identified via colonoscopy.…”
Section: Discussionmentioning
confidence: 97%
“…[36] Doi et al reported that 96.5% of patients with diverticular bleeding were successfully treated conservatively without early colonoscopy. [37] Recent reports regarding early colonoscopy for diverticular hemorrhage recommend conservative treatment except in severe cases, as the identification rate of SRH was 15% to 42% and the early and late rebleeding rates were not significantly different compared to patients who were treated conservatively. [36–39]…”
Section: Discussionmentioning
confidence: 99%